Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd003169.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal versus monofocal intraocular lenses after cataract extraction

Abstract: BACKGROUND: Good unaided distance visual acuity is now a realistic expectation following cataract surgery and intraocular lens (IOL) implantation. Near vision, however, still requires additional refractive power, usually in the form of reading glasses. Multiple optic (multifocal) IOLs are available which claim to allow good vision at a range of distances. It is unclear whether this benefit outweighs the optical compromises inherent in multifocal IOLs. OBJECTIVES: The objective of this review was to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 53 publications
2
94
0
Order By: Relevance
“…By analyzing the published literature, the Coch rane review prepared by Calladine et al [23] found only 16 papers reporting wellorganized and conducted studies, with 1,608 participants. The emerging evidence is that multifocal IOLs provide the same uncorrected and corrected dis tance vision as monofocal IOLs, but definitely better near vision.…”
Section: Visual Results and Patient Satisfactionmentioning
confidence: 99%
“…By analyzing the published literature, the Coch rane review prepared by Calladine et al [23] found only 16 papers reporting wellorganized and conducted studies, with 1,608 participants. The emerging evidence is that multifocal IOLs provide the same uncorrected and corrected dis tance vision as monofocal IOLs, but definitely better near vision.…”
Section: Visual Results and Patient Satisfactionmentioning
confidence: 99%
“…This finding was also consistent with previous studies, suggesting that multifocal IOLs were worthy of being more favored than monofocal IOLs. 15,[25][26][27] For the binocular distance vision of naked eyes and BCVA, no significant difference was observed in the effectiveness between multifocal and monofocal IOLs, as the ICERs indicated that multifocal IOLs were either too costly or were associated with a negative value. In addition, the ICERs of intermediate distance vision were in the second quadrant (dominant), suggesting that the multifocal IOL group was not better than the monofocal IOL group and an in-depth comparison was not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…They found that night driving was the only exception to total subjective satisfaction when postoperative quality of life was assessed. Although some authors have reported good clinical results with multifocal IOLs,14 15 many practitioners have still some concerns about the performance of this IOL modality due to the significant rates of postoperative halos and glare perception associated with some of these implants16 that may affect daily tasks and quality of life 17. Likewise, visual alterations induced by non-centred IOLs18 and the low tolerance to mild residual refractive errors that may yield to a significant reduction of UDVA19 are other concerns related to multifocal IOLs.…”
Section: Discussionmentioning
confidence: 99%